Diagnostic Test Development for Uncovering Student Misconceptions in Mechanical Wave Characteristics Topic - Nurohmah, Aneu Siti; Samsudin, Achmad; Rusnayati, Heni; Sozbilir, Mustafa (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
High school students have studied the characteristics of mechanical waves, including definitions, types, physical quantities, and properties of waves. However, many students still hold misconceptions about these concepts. This study aims to describe the validity and reliability of the Four-Tier Mechanical Wave Characteristics (FTMWC) diagnostic test instrument, developed to identify misconceptions among high school students regarding mechanical wave characteristics. The FTMWC was created through development research using the 4D model (Define, Design, Develop, Disseminate). The study involved 112 grade XI high school students who had already studied mechanical waves and were selected using purposive sampling. The instrument was analyzed using the Rasch Model with Winsteps software version 3.73. The validity of the FTMWC instrument was confirmed based on item dimensionality. The construct validity yielded a Cronbach's Alpha value of 0.61, indicating that the instrument sufficiently explains the interaction between participants and items. The item reliability was found to be 0.95, categorized as "very high." Conceptual analysis using Wright maps and Guttman scalograms revealed that the most common misconception was related to constructive interference in the sub-concept of wave properties. In conclusion, the FTMWC instrument is valid and reliable for assessing students' conceptions and identifying misconceptions about mechanical wave characteristics.